Territorio y prácticas socio-culturales en debate Aportes desde América Latina - Vargas Aguirre, Mónica; Basconzuelo, Celia; Quiroga, María Virginia; Buelvas, José David (Ariadna Ediciones, 2018)
One of the most interesting and distinctive notes of this book refers to its relevance with the time when writing against the consolidation of the extractivist accumulation model multiplies the struggles for land and territory, and proliferate studies on the subject